Modulation of endothelial cell migration by ER stress and insulin resistance: a role during maternal obesity? - Sáez, Pablo J.; Villalobos-Labra, Roberto; Westermeier, Francisco; Sobrevia, Luis; Farías-Jofré, Marcelo (Frontiers in Pharmacology, 2014)
Adverse microenvironmental stimuli can trigger the endoplasmic reticulum (ER) stress pathway, which initiates the unfolded protein response (UPR), to restore protein-folding homeostasis. Several studies show induction of ER stress during obesity. Chronic UPR has been linked to different mechanisms of disease in obese and diabetic individuals, including insulin resistance (IR) and impaired angiogenesis. Endothelial cell (EC) migration is an initial step for angiogenesis, which is associated with remodeling of existing blood vessels. EC migration occurs according to the leader-follower model, involving coordinated processes of chemotaxis, haptotaxis, and mechanotaxis. Thus, a fine-tuning of EC migration is necessary to provide the right timing to form the required vessels during angiogenesis. ER stress modulates EC migration at different levels, usually impairing migration and angiogenesis, although different effects may be observed depending on the tissue and/or microenvironment. In the context of pregnancy, maternal obesity (MO) induces IR in the offspring. Interestingly, several proteins associated with obesity-induced IR are also involved in EC migration, providing a potential link with the ER stress-dependent alterations observed in obese individuals. Different signaling cascades that converge on cytoskeleton regulation directly impact EC migration, including the Akt and/or RhoA pathways. In addition, ER is the main intracellular reservoir for Ca2+, which plays a pivotal role during EC migration. Therefore, ER stress-related alterations in Ca2+ signaling or Ca2+ levels might also produce distorted EC migration. However, the above findings have been studied in the context of adult obesity, and no information has been reported regarding the effect of MO on fetal EC migration. Here we summarize the state of knowledge about the possible mechanisms by which ER stress and IR might impact EC migration and angiogenesis in fetal endothelium exposed to MO during pregnancy